Root coverage in multiple recession defects (RT1) using the m-vista technique: a case report - Salinas Avila , Lucia (2026)
Gingival recession has been described as a common clinical condition, characterized by the apical displacement of the gingival margin and exposure of the root surface, which may lead to dental sensitivity, aesthetic impairmen, and an increased risk of root caries. Its treatment is determined by the classification and extent of the recession, as well as the patient's anatomical and systemic factors. The VISTA (Vestibular Incision Subperiosteal Tunnel Access) technique has been reported as an effective minimally invasive surgical option for managing multiple recessions, allowing for preservation of vascularization and flap stability. This case report describes the treatment of multiple RT1 gingival recessions using a modified technique (m-VISTA), which was supplemented with a subepithelial connective tissue graft and coronally anchored sutures. This technique was performed on a patient with multiple RT1 recessions in the anterior maxillary sector, and clinical follow-ups were conducted at 3 and 6 months, assessing root coverage, flap stability, and postoperative healing. Satisfactory root coverage was achieved, with an improvement in gingival biotype, adequate tissue stability, and no surgical complications. Additionally, the patient reported improved aesthetics and reduced sensitivity. Overall, the clinical findings support the use of the m-VISTA technique as a safe, predictable, and minimally invasive surgical alternative for treating multiple RT1 gingival recessions, with good patient acceptance.